Discrete-Time Impedance Model-Based Dynamic Analysis and Parameter Design for VSG-Controlled Grid-Forming DG System - Thiago F. do Nascimento; Josenalde B. Oliveira; Elmer R. L. Villarreal; Andrés O. Salazar (Energies, 2025)
The virtual synchronous generator (VSG) scheme has proven to be an attractive solution in grid-forming converter applications integrated into distributed generation (DG) systems. Thus, this paper presents the dynamic performance of power flow control using the VSG approach under Thevenin impedance variations seen by the grid-forming converter. The dynamic analysis is based on a discrete-time model that describes the power flow transient characteristics of the system operating in medium- and high-voltage networks. Based on the proposed model, a controller design procedure for the discrete-time VSG scheme is presented. This methodology aims to assist researchers in implementing VSG control in digital environments. Then, the Thevenin impedance parameters’ influence on the discrete-time VSG strategy dynamic performance is discussed. The VSG technique’s performance in different operating scenarios is assessed by means of simulation results. A case study is provided to validate the effectiveness of the theoretical analysis and the discrete-time VSG control scheme. The results assess the effectiveness of the theoretical analysis performed.